Increase in corneal epithelial cell size with extended wear soft contact lenses depends on continuous wearing time. Issue 2 (February 1996) - Tsubota, K; Hata, S; Toda, I; Yagi, Y; Sakata, M; Shimazaki, J
Abstract : AIM: Although 1 week of continuous wearing time (CWT) is recommended for extended wear soft contact lenses (EWSCL), there have been few studies concerning the appropriateness of this or other CWTs. The current study was undertaken to examine the effect of various CWTs on the cornea by observing the corneal epithelium. METHODS: Specular microscopy was used to evaluate corneal epithelial changes induced by EWSCL in 19 myopic patients (24.0 (SD 6.7) years), divided into four groups: CWT of 0, 1, 3, and 6 days. RESULTS: The initial mean cell area was 628.2 (13.4) micron2. After 6 months this was 629.3 (28.6) micron2 for daily wear (ns), and 660.0 (40.9) micron2, 727.7 (49.6) micron2 (p < 0.01), and 815.5 (67.2) micron2 (p < 0.01) for CWT of 1, 3, and 6 days, respectively (p < 0.01). CONCLUSION: These findings indicate that the corneal epithelium changes proportionally with the CWT; the shorter the CWT, the better the epithelial morphology. This suggests that the CWT for EWSCL be minimised, so as to reduce the potential risk of contact lens related problems.